The moral economy of 'respect' in Chilean society - Orchard, Macarena (2019)
This thesis interrogates the experience of respect and disrespect in everyday life from a sociological perspective, with the aim of elucidating the relationship between respect and inequality. It involves a theoretical exploration of the phenomenon of respect as well as an empirical study, which focuses on Chilean society. This study analyses the meanings, practices and narratives associated with, as well as the distribution of, the experience of respect and disrespect in Chile. It involves a mixed method study which includes secondary data analyses together with semi-structured interviews of people of different ages, sex and class in Santiago de Chile. Based on both deductive and inductive criteria, the thesis suggests that respect is the norm, the language and the practice through which we communicate value to others, which is culturally situated and changes historically according to how value is defined in any given context. It claims that there are three main types of respect: categorical, positional and performance and it argues that looking at the tensions between these three types of respect is a fruitful way to read cultural changes regarding the expectations of treatment that are formed in social interactions. Following this approach, the thesis depicts the ‘moral economy of respect’ in Chile, by describing how the participants experience different types of respect. It demonstrates that the experience of respect and disrespect is unequally distributed, but the structure of advantage and disadvantage involved in this experience becomes evident when looking at the process, rather than the outcome, of getting respect. The thesis identifies two main processes of securing respect: earning and commanding respect, both of which demonstrate the importance of agency in the achieving of respect. Finally, the thesis concludes by suggesting that studying respect is productive in the understanding of the experience, consequences and reproduction of inequality.